Q: 9b plus 40 equals 13b what is the answer to that?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9b-13b= -4b -4b = 40 Divide both sides by -4 b = -10

Gh

15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6

3A + 9B = 3(A + 3B)

10b

Related questions

9b-13b= -4b -4b = 40 Divide both sides by -4 b = -10

Gh

15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6

9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)

3A + 9B = 3(A + 3B)

The simplified expression is -9a -9b.

6B, 7B, 8B, 9B, 10B, 11B, 12B, 13B, 14B, 15B, 16B, 17B, 18B, 19B

There are 3 terms in the given expression of 6a+9b+15

All the terms in b add to 11, so 11b = 132 making b = 12

You would factor 3a + 9b as: 3(a+3b)

10b

(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b